Recent Developments in Plasmonic Alloy Nanoparticles: Synthesis, Modelling, Properties and Applications - Coviello, Vito; Forrer, Daniel; Amendola, Vincenzo (Chemphyschem, 2022)
Despite the traditional plasmonic materials are counted on one hand, there are a lot of possible combinations leading to alloys with other elements of the periodic table, in particular those renowned for magnetic or catalytic properties. It is not a surprise, therefore, that nanoalloys are considered for their ability to open new perspectives in the panorama of plasmonics, representing a leading research sector nowadays. This is demonstrated by a long list of studies describing multiple applications of nanoalloys in photonics, photocatalysis, sensing and magneto‐optics, where plasmons are combined with other physical and chemical phenomena. In some remarkable cases, the amplification of the conventional properties and even new effects emerged. However, this field is still in its infancy and several challenges must be overcome, starting with the synthesis (control of composition, crystalline order, size, processability, achievement of metastable phases and disordered compounds) as well as the modelling of the structure and properties (accuracy of results, reliability of structural predictions, description of disordered phases, evolution over time) of nanoalloys. To foster the research on plasmonic nanoalloys, here we provide an overview of the most recent results and developments in the field, organized according to synthetic strategies, modelling approaches, dominant properties and reported applications. Considering the several plasmonic nanoalloys under development as well as the large number of those still awaiting synthesis, modelling, properties assessment and technological exploitation, we expect a great impact on the forthcoming solutions for sustainability, ultrasensitive and accurate detection, information processing and many other fields. Developing plasmonic nanoalloys: In this review, we give a general overview of the most recent advances in synthesis, modelling, properties assessment, and technological application of plasmonic nanoalloys.